Analisis Potensi Bahaya K3 Menggunakan Metode HIRARC Pada Bagian Boiler PLTU Nii Tanasa Kendari Di Kecamatan Lalonggasumeeto Kabupaten Konawe Tahun 2023 - Wiradara, Adinda Gadis; G., Fifi Nirmala; Saptaputra, Syawal kamiluddin (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
HIRARC is a document that contains hazard identification, risk assessment and risk control in order to reduce the occurrence of occupational safety and health disturbances. The type of research used is qualitative with a descriptive approach. The research aims to explain the value of the risks contained in each work area by describing the work safety analysis process by determining the level of likelihood and severity of each risk. Based on interviews and observations conducted by researchers in the Boiler section of PLTU Nii Tanasa Kendari, there are several potential dangers ranging from physical, mechanical, chemical, electrical, to ergonomic dangers. The results of the analysis of potential hazards show a low risk of 9 types of danger, a moderate risk of 7 types of danger, a high risk of 8 types of danger.The controls used are technical engineering such as providing fire extinguishers and first aid kits, installing handrails and guardrails to anticipate falls from heights, and providing insulation and dampening for equipment that is at high risk of causing work accidents. Administrative controls such as providing work instructions and SOPs, cleaning work environment areas and using PPE.